2011
DOI: 10.1038/emboj.2011.44
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis of EphA receptors is essential for the proper development of the retinocollicular topographic map

Abstract: Endocytosis of Eph-ephrin complexes may be an important mechanism for converting cell-cell adhesion to a repulsive interaction. Here, we show that an endocytosisdefective EphA8 mutant forms a complex with EphAs and blocks their endocytosis in cultured cells. Further, we used bacterial artificial chromosome transgenic (Tg) mice to recapitulate the anterior4posterior gradient of EphA in the superior colliculus (SC). In mice expressing the endocytosis-defective EphA8 mutant, the nasal axons were aberrantly shifte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 44 publications
2
35
0
Order By: Relevance
“…37,38 To examine the expression patterns of ephrin-A5 or EphA7 along the DM, we generated bacterial artificial chromosome (BAC) transgenic lines in which the ephrin-A5 or EphA7 promoter drives expression of the LacZ reporter, as described (Supplementary Figure 1G). 39,40 Consistent with previous studies, X-gal (X-gal, 5-bromo-4-chloro-3-indolyl-b-D-galactopyranoside) staining of eA5-LacZ BAC embryos at E11.5 revealed that LacZ expression recapitulated the expression pattern of ephrin-A5 in brain regions such as the posterior midbrain, the DM of the diencephalon, and the medial region of the posterior telencephalon (Figures 2a and b). Similarly, reporter expression of the EphA7-LacZ BAC embryo is consistent with a previous report showing that EphA7 is expressed in the DM of the diencephalon and the lateral region of the posterior telencephalon (Figures 2i and j).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…37,38 To examine the expression patterns of ephrin-A5 or EphA7 along the DM, we generated bacterial artificial chromosome (BAC) transgenic lines in which the ephrin-A5 or EphA7 promoter drives expression of the LacZ reporter, as described (Supplementary Figure 1G). 39,40 Consistent with previous studies, X-gal (X-gal, 5-bromo-4-chloro-3-indolyl-b-D-galactopyranoside) staining of eA5-LacZ BAC embryos at E11.5 revealed that LacZ expression recapitulated the expression pattern of ephrin-A5 in brain regions such as the posterior midbrain, the DM of the diencephalon, and the medial region of the posterior telencephalon (Figures 2a and b). Similarly, reporter expression of the EphA7-LacZ BAC embryo is consistent with a previous report showing that EphA7 is expressed in the DM of the diencephalon and the lateral region of the posterior telencephalon (Figures 2i and j).…”
Section: Resultssupporting
confidence: 90%
“…ephrin-A5. 39 For this purpose, a targeting vector consisting of floxed green fluorescent protein (GFP) and ephrin-A5-Fc was inserted into the first exon of ephrin-A5 BAC in which only GFP expression occurs because of stop signals between GFP and ephrin-A5-Fc (Figure 3a). Transgenic mice carrying a recombinant BAC, eA5-eA5Fc, were crossed with Wnt1-Cre to induce specific expression of ephrin-A5-Fc in the DM of the diencephalon and mesencephalon ( Figure 3b).…”
Section: Resultsmentioning
confidence: 99%
“…We thus used ephrin A5 (Efna5) BAC transgenic lines that contain sufficient cis-acting elements to drive expression of GFP in the pattern of endogenous Efna5 expression (Yoo et al, 2011). In horizontal sections along the naso-temporal axis, we observed that Efna5 expression begins in the optic vesicle at E9.5.…”
Section: Resultsmentioning
confidence: 99%
“…Ephrin A5 BAC transgenic mice expressing GFP have been previously described (Yoo et al, 2011). To generate the EphB2-GFP BAC targeting vector, we amplified homologous arms A (1008 bp) and B (909 bp) flanking the mouse Ephb2 translation start site (ATG) using PCR with the following primers: 5′-GGCCAAGTCGGCCGAGTA-GGGGCTGTCGCTA-3′ (forward primer for A arm); 5′-GAGCTCTGC-TGCGCTGCCCGGAGCCT-3′ (reverse primer for A arm); 5′-ATGCATCATCTTGCCGAGGCTTTGTA-3′ (forward primer for B arm); and 5′-ATGCATAATTCGACCCATCTGGCTTC-3′ (reverse primer for B arm).…”
Section: Bac Modification Transgenic and Knockout Micementioning
confidence: 99%
“…Eph-ephrin signalling often initiates contact repulsion, causing de-adhesion, collapse of cell processes, and cell detachment. However, the initial binding between Eph and ephrins is high affinity, forming a stable linkage between the interacting proteins [47,369]. To counter this attachment, ephrins bind a protease that becomes activated by Eph-ephrin signalling [119].…”
Section: Overview: Ephs Ephrins and Topographic Mapsmentioning
confidence: 99%